Factors Influencing Purchase Intention with Brand Awareness as a Mediator on Fabric Product in Textile Industry - Hapsari, Yustisiana Tika; Belgiawan, Prawira Fajarindra (Jurnal Doktor Manajemen (JDM), 2025)
The rapid growth of the textile and fashion industry in Indonesia is increasingly driven by digital transformation and changes in consumer behavior. MSTEX, a local textile company established in 2013, is known for its affordable prices and consistent fabric quality. However, the company faces challenges in strengthening brand awareness and attracting new customers in the online B2B market. This study aims to analyze how social media marketing, word-of-mouth, product attributes (price and quality), and brand awareness influence purchase intention. A quantitative method approach is used in this study, while quantitative data are collected through a questionnaire involving 201 active social media users, resellers, and business customers. Data are analyzed using IBM SPSS 23 and SMART PLS (PLS-SEM) to test the hypotheses and examine the structural relationships.The findings show that word-of-mouth significantly influences brand awareness, while social media marketing does not. Product quality and price also influence customer purchase intention. In addition, brand awareness has a strong positive effect on purchase intention. This study contributes theoretically by supporting existing consumer behavior and brand equity models and expands the application of digital marketing constructs in B2B textile settings. From a managerial perspective, the results offer insights into how textile businesses can prioritize marketing strategies that resonate with their target markets and enhance brand visibility in the digital space.